Oral microbiota in xerostomia patients - A preliminary study - Chen-Tsung Weng; Shir-Ly Huang; Hui-Wen Yang; Chih-Chin Kao; Cheng-Chung Wei; Yu-Feng Huang (Elsevier, 2022)
Background/purpose: The estimated prevalence of xerostomia (lack of saliva) ranges from 10% to 50% of the general population. The oral cavity provides a multivariant environmental habitat to over 700 species of bacteria and fungi. We hypothesized that xerostomia will alter the composition of oral microbiota. Material and methods: Nineteen xerostomia patients and 10 healthy normal volunteers were studied for the oral microbiota. Gingival plaques were collected and microbiota were detected using bacterial 16S ribosomal RNA and analyzed based on the levels of phylum and class. Results: In all cases, phyla of Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria make up to 100% of oral microbiota at phylum level. Analyzing individual phylum, presence of Bacteroidetes in xerostomia patients and normal subjects were 23.12 ± 2.56% and 23.23 ± 2.58%, respectively. Mean percentage presence of Firmicutes phylum in xerostomia patients and normal subjects were 18.94 ± 1.83% and 14.06 ± 0.98%, respectively. Statistically significant difference was not observed between xerostomia patients and normal subjects in this study. Conclusion: These observations revealed obvious but not statistically significant changes in oral major microorganism phylum between xerostomia patients and normal subjects in this study. More samples are needed to verify the current results and to use oral microbiota as a tool in the diagnosis of xerostomia.